2018
DOI: 10.4314/sajas.v48i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the uterine involution and dimensions, hormonal response and reproductive performance of pyometric and healthy dairy cows treated with Dinoprost

Abstract: The aim of the present study was to investigate the effects of a PGF 2α analogue (Dinoprost) on involution of the puerperal uterus, especially with pyometra during 35 to 45 days postpartum in multiparous high yielding Holstein dairy cows. At days 40 ± 5 postpartum, 1250 cows were ultrasonographically examined. Fifty cows were diagnosed as pyometric. Fifty pyometric and 50 clinically healthy cows were assigned randomly to one of four groups. Groups were: 1.) Pyometric+Dinoprost cows (PD, n = 25 treated with 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It has been reported that the PGF 2 α the most effective drug for metritis (19), while others showed no improvement of the subclinical metritis (20,21) . It has been observed that administration of 25 mg/im of Dinoprost (synthetic PGF 2 α) had an effect on reduction of the size of the uterus (22) . The low response in T 1 and T 2 which treated with lugol's Iodine and Lotagen respectively it might be due to that intrauterine infusions treated with these antiseptics leads to irritation and necrosis of endometrial wall and may cause damages to the endometrial glands.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the PGF 2 α the most effective drug for metritis (19), while others showed no improvement of the subclinical metritis (20,21) . It has been observed that administration of 25 mg/im of Dinoprost (synthetic PGF 2 α) had an effect on reduction of the size of the uterus (22) . The low response in T 1 and T 2 which treated with lugol's Iodine and Lotagen respectively it might be due to that intrauterine infusions treated with these antiseptics leads to irritation and necrosis of endometrial wall and may cause damages to the endometrial glands.…”
Section: Resultsmentioning
confidence: 99%
“…Estrus detection was performed by two technicians every 3 h for at least 20 min during each observation. Estrus was confirmed by transrectal palpation before AI as previously described (López-Gatius and Camón-Urgel, 1991;Masoumi et al, 2018). Cows confirmed in estrus were inseminated, according to the am/pm rule, with semen from sires available commercially.…”
Section: Methodsmentioning
confidence: 99%
“…Melendez et al (2004) reported that at 8 d postpartum, two doses of PGF2α 8 h apart in primiparous Holstein cows diminished the diameter of the uterine horns. Masoumi et al (2018) observed that 25mg PGF2α injection led to uterotonic effects, which may aid accelerate uterine involution in puerperal dairy cows. PGF2α is commonly used during early postpartum to facilitate uterine involution in dairy cows (Salasal andMokhtari, 2011 andJeremejeva et al, 2012).…”
Section: Effect Of Treatment With Oxytetracycline and Prostaglandinf2...mentioning
confidence: 97%